Anmeldelse af L. E. Andersen og Hans Hauge (red.): Tekst og trope - Sørensen, Marianne (Passage - Tidsskrift for litteratur og kritik, 1988)
Anmeldelse af L. E. Andersen og Hans Hauge (red.): Tekst og trope